A norovirus GII.P21 outbreak in a boarding school, Austria 2014. (August 2015) - Lin, Yung-Ching; Hipfl, Elisabeth; Lederer, Ingeborg; Allerberger, Franz; Schmid, Daniela
Highlights: We applied day-specific cohort analyses and calculated risk ratios of food exposures on each day in developing symptoms within the following 2 days. We detected norovirus in environmental swabs and stool specimens. The noroviruses from the stool specimens of cases and food handlers were of the same genotype, GII.P21. The kebab prepared by norovirus-positive, asymptomatic restaurant workers was the most likely source of the outbreak. Summary: Objectives: An Austrian boarding school reported a cluster of gastroenteritis on January 10, 2014. Environmental swabs from the school cafeteria and a nearby kebab restaurant tested positive for norovirus. The outbreak was investigated to identify its source(s). Methods: An outbreak case was defined as a student or staff member with diarrhoea or vomiting that developed between January 7 and 13. Details on food exposure were collected via a self-administered questionnaire; risk ratios (RR) and 95% confidence intervals (CI) were calculated. Norovirus from the stool specimens of cases and asymptomatic kebab restaurant workers were genotyped. Results: Twenty-eight cases were identified among 144 persons (attack rate 19%). The outbreak emerged and peaked on January 9, and ended on January 12. Compared to those who did not eat kebab, those who ate kebab on 7, 8, and 9 January were respectively 11 (95% CI 4.2–28), 6.7 (95% CI 3.4–13), and 9.3 (95% CI 4.0–22) times more likely to develop disease within the following 2 days. Stool specimens from three cases and three restaurant workers were positive for norovirus GII.P21. Conclusions: The kebab prepared by norovirus-positive restaurant workers was the most likely source of the outbreak. It is recommended that food handlers comply strictly with hand hygiene and avoid bare-handed contact with ready-to-eat food to minimize the risk of food-borne infection.